2004
DOI: 10.1016/j.cub.2004.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Taste Cues Modulate Olfactory Learning in C. elegans by an Occasion-Setting Mechanism

Abstract: Manipulations of context can affect learning and memory performance across species in many associative learning paradigms. Using taste cues to create distinct contexts for olfactory adaptation assays in the nematode Caenorhabditis elegans, we now show that performance in this associative learning paradigm is sensitive to context manipulations, and we investigate the mechanism(s) used for the integration of context cues in learning. One possibility is that the taste and olfactory stimuli are perceived as a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 18 publications
0
30
0
1
Order By: Relevance
“…It has been reported that gpc-1 is involved in salt chemotaxis plasticity ( Jansen et al 2002), while no olfactory adaptation defect was observed in gpc-1 mutants ( Jansen et al 2002;Law et al 2004). Thus, this is the first report that C. elegans gpc-1 is involved in olfactory adaptation.…”
Section: Resultsmentioning
confidence: 53%
“…It has been reported that gpc-1 is involved in salt chemotaxis plasticity ( Jansen et al 2002), while no olfactory adaptation defect was observed in gpc-1 mutants ( Jansen et al 2002;Law et al 2004). Thus, this is the first report that C. elegans gpc-1 is involved in olfactory adaptation.…”
Section: Resultsmentioning
confidence: 53%
“…Following odorant habituation, expression of the learned behavior can be modulated by contextual cues present during conditioning. Law et al (2004) found that worms exposed to an odorant in the presence of a taste cue showed enhanced retention of olfactory habituation when challenged in the presence of that same cue (Law et al 2004). Furthermore, Bettinger and McIntire (2004) demonstrated that worms previously adapted to an odorant under the influence of ethanol displayed decremented responses to that odorant only when intoxicated.…”
Section: Effect Of Context On Chemosensory Habituationmentioning
confidence: 99%
“…Anderson et al (Anderson et al, 2007) assayed thermotaxis on a steeper gradient than we did, and both prior studies (Anderson et al, 2007;Jurado et al, 2010) used assay plates comprised of different media than the NGM agar plates on which the worms were reared, which might have led to a contextspecific association of food, temperature and medium. Such circumstances could potentially change the association of food and temperature, and block thermophilic behaviour in some assay conditions (Law et al, 2004).…”
Section: Variation Within C Elegans For Temperature-dependent Behaviourmentioning
confidence: 99%